CHEATING DETECTION AND CHEATER IDENTIFICATION IN CRT-BASED SECRET SHARING SCHEMES - Pasailă, Daniel; Alexa, Vlad; Iftene, Sorin (International Journal of Computing, 2010)
In this paper we analyze the cheating detection and cheater identification problems for the secret sharing schemes based on the Chinese remainder theorem (CRT), more exactly for Mignotte [1] and Asmuth-Bloom [2] schemes. We prove that the majority of the solutions for Shamir’s scheme [3] can be translated to these schemes and, moreover, there are some interesting specific solutions.